Accuracy and Reliability of 3D Imaging for Facial Movement Evaluation: Validation of the VECTRA H1. Issue 2 (23rd February 2023) - Kelly, Brendan C.; Pyne, Justin M.; Rosvall, Brandon R.; Song, Jin Soo; Côté, David W. J.
Abstract : Background: Three-dimensional imaging can be used to obtain objective assessments of facial morphology that is useful in a variety of clinical settings. The VECTRA H1 is unique in that it is relatively inexpensive, handheld, and does not require standardized environmental conditions for image capture. Although it provides accurate measurements when imaging relaxed facial expressions, the clinical evaluation of many disorders involves the assessment of facial morphology when performing facial movements. The aim of this study was to assess the accuracy and reliability of the VECTRA H1, specifically when imaging facial movement. Methods: The accuracy, intrarater, and interrater reliability of the VECTRA H1 were assessed when imaging four facial expressions: eyebrow lift, smile, snarl, and lip pucker. Fourteen healthy adult subjects had the distances between 13 fiducial facial landmarks measured at rest and the terminal point of each of the four movements by digital caliper and by the VECTRA H1. Intraclass correlation and Bland–Altman limits of agreement were used to determine agreement between measures. The agreement between measurements obtained by five different reviewers was evaluated by intraclass correlation to determine interrater reliability. Results: Median correlation between digital caliper and VECTRA H1 measurements ranged from 0.907 (snarl) to 0.921 (smile). Median correlation was very good for both intrarater (0.960–0.975) and interrater reliability (0.997–0.999). The mean absolute error between modalities, and both within and between raters was less than 2 mm for all movements tested. Conclusion: The VECTRA H1 met acceptable standards for the assessment of facial morphology when imaging facial movements.